Economic impact of Juvenile Idiopathic Arthritis: a systematic review - García Rodríguez, Fernando; Gamboa Alonso, Augusto; Jiménez Hernández, Sol; Ochoa Alderete, Lucero; Barrientos Martínez, Valeria Alejandra; Alvarez Villalobos, Neri Alejandro; Luna Ruíz, Gabriela Andrea; Peláez Ballestas, Ingris; Villarreal Treviño, Ana Victoria; De la O Cavazos, Manuel Enrique; Rubio Pérez, Nadina (BioMed Central Ltd., 2021)
Abstract Background Juvenile Idiopathic Arthritis (JIA) requires complex care that generate elevated costs, which results in a high economic impact for the family. The aim of this systematic review was to collect and cluster the information currently available on healthcare costs associated with JIA after the introduction of biological therapies. Methods We comprehensively searched in MEDLINE, EMBASE, Web of Science, Scopus, and Cochrane Databases for studies from January 2000 to March 2021. Reviewers working independently and in duplicate appraised the quality and included primary studies that report total, direct and/or indirect costs related to JIA for at least one year. The costs were converted to United States dollars and an inflationary adjustment was made. Results We found 18 eligible studies including data from 6,540 patients. Total costs were reported in 10 articles, ranging from $310 USD to $44,832 USD annually. Direct costs were reported in 16 articles ($193 USD to $32,446 USD), showing a proportion of 55 to 98 % of total costs. Those costs were mostly related to medications and medical appointments. Six studies reported indirect costs ($117 USD to $12,385 USD). Four studies reported costs according to JIA category observing the highest in polyarticular JIA. Total and direct costs increased up to three times after biological therapy initiation. A high risk of reporting bias and inconsistency of the methodology used were found. Conclusion The costs of JIA are substantial, and the highest are derived from medication and medical appointments. Indirect costs of JIA are underrepresented in costs analysis.